Orthophotograph production in urban areas - Skarlatos, Dimitrios (My University, 1999)
This paper investigates possible solutions to the problem of urban orthophotography. Extensive work has been carried out to attain the best possible results, using all the existing software in the Department of Geomatic Engineering, University College London. Two of the most promising methods, which yield the best results, are analysed further. New routines were written in C language, as additions to the existing software, to allow for the special problems that arise in urban areas. The final results overcome the problem of double mapping (or occlusions) and will potentially enable even greater success to be achieved. A simple accuracy assessment of the results has been made. Difficulties and current limitations are analysed and presented.
Keywords: Orthophotography; Urban imagery